Fatigue crack growth analysis of stainless steel under mode 1 - Ahmad Azam Azizan, Azlan (2010)
Stainless steel is widely used in the industries nowadays due to their good properties of resistance to corrosion and rust. Due to its application in many industries, an analysis of fatigue crack growth was carried out to study the effect of stress ratio. The study of fatigue crack growth is important since fatigue has become a critical issue in industries that plague any structures that is subjected to cyclic and variable loading. A necessary analysis of fatigue crack growth need to be done to study the behaviour of fatigue crack growth. The effect of stress ratio on fatigue crack growth can affect the behavior of fatigue crack growth. In the project, three different stress ratios were used to investigate the effect of stress ratio towards crack growth. As the stress ratio increase, the stress intensity threshold and fracture toughness will decrease. This shows that an increasing stress ratio will lead to material failure. This happens when the stress intensity factor has entered the critical region where it exceeds the fracture toughness value. To remain the material unbroken or fail, the stress intensity factor value must not exceed the value of stress intensity threshold where below the stress intensity threshold value, the material remains stable. An analysis of fatigue crack growth was done using MSC software where the stress analysis is done using MSC PATRAN and MSC NASTRAN. After the results of stress analysis were obtained, the analysis of fatigue crack growth with different stress ratio was done using MSC FATIGUE software. Life prediction of the material is determined using Modified Paris Law equation of Fracture Mechanics. At certain level of stresses, below the endurance limit of the material, the effect of stress ratio does not affecting the life of the material. This is because the stress is not big enough to break the material.